Subject and melancholy in Gejza Vámoš’s Work - Tomáš Horváth (Slovenska Literatura, 2015)
Alongside partial interpretation of the debut collection of proses by Gejza Vámoš Editino očko (Edita´s little eye, 1925), the paper is focused on modelling a constitution as well as decomposing some of the modalities of the literary subject, also defined in terms of literary movement. Attention is also paid to how these ways of representing the literary subject in Vámoš´s texts are related to the subject´s mood of melancholy. Vámoš´s paranoid character (of the short story Paranoik, The Paranoid) cannot live, enjoy life because he lives in „death´s coldness“, which makes him already a corpse, although he is still alive – the future of the death is present during his life: therefore a paranoid lives his life in the melancholy mode. A paranoid´s abnormality segregates him from the low crowd (misera plebs) of people who forget about their mortality. Vámoš´s premises of biological philosophy suggest that a paranoid cannot be an exclusive subject, „a spiritual aristocrat“: it is because at the level of a biological species in Vámoš´s philosophy there occurrs destruction, dissolution of an individual in general. An individual helps the actual biological species perceive and feel itself, and it is the species that becomes the true subject, which is moulded into its manifestations, unimportant individuals. This is where Vámoš´s melancholy springs from. The eternity of life at the cosmological-biological level means the eternity of suffering at the level of individuals: eternal life (at the cosmological level), which cannot be ended (by a ridiculously feeble suicide of an individual), will eternally reproduce the mortality of individual atoms, individuals.